Update on amyotrophic lateral sclerosis genetics - Brenner, David; Weishaupt, Jochen H. (Current opinion in neurology, 2019)
Purpose of review - The fatal motoneuron disease amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder with a high contribution of genetic factors to pathogenesis, in probably both familial and sporadic ALS cases. State-of-the art sequencing techniques continue to reveal novel monogenic causes for ALS, risk factors and modifiers. This leads to an improved genotype/phenotype correlation and is becoming increasingly relevant for genetic diagnosis, counseling and therapy. The first gene-specific therapies are being tested in ongoing clinical trials. Consequently, this review aims to summarize the most important aspects of ALS genetics of the past 2 years. - Recent findings - Most recent disease gene discoveries in the field of ALS constitute the genes KIF5A, ANXA11, GLT8D1 and TIA1, as well as an array of novel risk factors and modifiers. Increasing evidence suggests that even ALS mutations with high penetrance can co-occur with additional mutations in other known ALS genes, suggesting a relevant role of digenetic or polygenetic modes of inheritance. Genotype/phenotype correlation reveals clinical pleiotropy for several ALS genes, which can be linked, for example, to ataxia or Parkinsonian syndromes beyond classical ALS and frontotemporal dementia (FTD) phenotypes. - Summary - The field of ALS continues to develop rapidly with multiple disease gene discoveries per year. The relevance of these findings for genetic counseling and diagnosis is obvious. With gene-specific therapies being tested in a clinical setting, the relevance of genetic aspects of ALS is increasing and likely to be linked to therapeutic consequences in the near future.